Clofazimine, but Not Isoniazid or Rifampicin, Augments Platelet Activation in vitro - Anderson, Ronald; Theron, Annette J.; Nel, Jan G.; Durandt, Chrisna; Cholo, Moloko C.; Feldman, Charles; Tintinger, Gregory R. (Frontiers in Pharmacology, 2018)
Although the inclusion of clofazimine in the chemotherapeutic regimens of patients with multidrug-resistant (MDR) tuberculosis (TB) has contributed to improved outcomes, concerns remain about the cardiotoxic potential of this agent. Accordingly, the current study was undertaken with the primary objective of investigating the effects of clofazimine on the reactivity of human platelets in vitro as a possible, seemingly unexplored, mechanism of cardiotoxicity.Platelet-rich plasma (PRP) prepared from the blood of healthy, adult humans was treated with clofazimine (0.625-10 mg/L), or the primary anti-TB agents, isoniazid and rifampicin (final concentrations of 5 and 10 mg/L for each), followed by addition of either adenosine 5-diphosphate (ADP) or thrombin and measurement of platelet activation according to the magnitude of expression of CD62P (P-selectin) using flow cytometry. Clofazimine, but neither isoniazid nor rifampicin, caused dose-related potentiation of both ADP- and thrombin-activated expression of CD62P by platelets, achieving statistical significance at threshold concentrations of 0.625 and 2.5 mg/L respectively. These stimulatory effects of clofazimine on platelet activation were partly attenuated by pre-treatment of PRP with the membrane-stabilising agent, α-tocopherol. Clofazimine, at concentrations within the therapeutic range, augments platelet activation in vitro, probably by a mechanism linked to membrane destabilisation, which, if operative in vivo, may exacerbate the risk of TB-associated cardiovascular disease.